Adnexal masses in pregnancy: An updated review - Abdullah M Hakoun (Thieme Medical and Scientific Publishers Pvt. Ltd., 2017)
Adnexal masses in pregnancy are not commonly encountered. The majority of these masses are discovered incidentally during routine follow-up. However, some of these masses become symptomatic due to their size, location, and impingement of adjacent structures. Several diagnostic modalities can be utilized for the detection of adnexal masses with different sensitivity and specificity rates. The differential diagnosis of adnexal masses discovered during pregnancy is broad and includes both benign and malignant lesions. The management of such lesions has been a subject of debate for years with no consensus regarding the best management plan. Tumor size, site, and the trimester of mass detection are all crucial in management. In this account, we review adnexal masses discovered in pregnancy, the diagnostic modalities utilized for detecting these lesions, their differential diagnosis, and management strategies.